TREATMENT FOR STUDENTS WITH LEARNING DISABILITY THAT CAN BE DONE BY BOTH TEACHERS AND PARENTS: A LITERATURE REVIEW - Rusmono, Danny (JKKP (Jurnal Kesejahteraan Keluarga dan Pendidikan), 2019)
Inclusion education program has been implemented in Indonesia, which means schools are obliged to accept students with special needs. Students of said category perieved as a particular burden by their teachers. Teachers said that it was because they are lacking in experience to handle said students and they did not graduate from special education program in college. Aside from teachers, there are parents who are still lacking in information about the condition of their children. The present reserarch aims to find treatments suitable for teachers and parents to do to children with learning disabilities. The search of e-literatures was conducted to identify journals published from 2009 to 2019 concerning treatments that are suitable for teachers and parents to do. Electronic databases used were ScienceDirect, Proquest, Springer and SAGE. There were 6 studies used in this research after excluding studies that did not match to criteria used in this review. Treatments that can be done by both teachers and parents to students with learning disabilities are Group Intervention, Teacher-made Instruction Material, Homeschooling, Phonology and Orthography. The outcome of using those treatments is that students show improved skills to do what they have been struggling with and catching up with their peers. Abstrak Pendidikan inklusi sudah diberlakukan di Indonesia. Artinya semua sekolah wajib menerima siswa berkebutuhan khusus. Guru mendapati siswa berkebutuhan khusus membawa beban dalam pengajarannya. Hal tersebut dikarenakan guru yang kurang berpengalaman atau guru tidak berasal dari pendidikan luar biasa. Selain guru yang kurang dapat menangani siswa berkebutuhan khusus, orang tua juga masih ada yang kurang memahami kondisi anaknya. Penelitian ini bertujuan untuk menemukan penanganan apa yang bisa dilakukan oleh orang tua dan guru. Pencarian literatur elektronik yang diterbitkan dalam 10 tahun terakhir mengenai penanganan yang dapat dilakukan oleh orang tua dan guru. Database elektronik yang digunakan adalah ScienceDirect, Proquest, Springer, Sage. Ada 6 studi yang digunakan setelah adanya seleksi menurut kriteria yang sudah ditetapkan. Ada beberapa penanganan yang dapat dilakukan bagi siswa dengan learning disability seperti group intervention, teacher-made instruction material, homeschooling, phonology dan ortography. Dari penanganan yang telah disebutkan, hasilnya adalah siswa dengan learning disability menunjukkan kemampuan belajar yang membaik, dan mampu mengejar ketertinggalan mereka dengan teman sebayanya.